2021
DOI: 10.1186/s40634-021-00364-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of femoral tunnel exit on the 3D graft bending angle in anterior cruciate ligament reconstruction

Abstract: Purpose To quantify the influence of the femoral tunnel exit (FTE) on the graft bending angle (GBA) and GBA-excursion throughout a full range of motion (ROM) in single-bundle anterior cruciate ligament (ACL) reconstruction. Methods Three-dimensional (3D) surface models of five healthy knees were generated from a weight-bearing CT obtained throughout a full ROM (0, 30, 60, 90, 120°) and femoral and tibial ACL insertions were computed. The FTE was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…1,18,22 This apparent discrepancy may be a result of different primary etiologic factors at play. Whereas the tendon graft is bent at the femoral aperture by approximately 70 , 15,21,33 in the tibia the graft exits the tunnel almost straight, irrespective of the knee flexion angle. Consequently, graft tension yields higher graft-bone contact pressure in the femoral tunnel, which may induce cell necrosis and subsequent bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…1,18,22 This apparent discrepancy may be a result of different primary etiologic factors at play. Whereas the tendon graft is bent at the femoral aperture by approximately 70 , 15,21,33 in the tibia the graft exits the tunnel almost straight, irrespective of the knee flexion angle. Consequently, graft tension yields higher graft-bone contact pressure in the femoral tunnel, which may induce cell necrosis and subsequent bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…The ankle JL was defined as the average plane of five surface registration points on the tibial plafond in a standardized fashion (two at the anterior ridge, two at the posterior ridge and one at the center) (Fig. 2 ) as described by Hodel et al [ 10 ] The approximation of the JL based from the contralateral side was measured in mm in direction of the anatomical tibia axis (z-axis) (positive values indicating an elevation of the JL, negative values indicating a distalisation). In addition, the mean absolute error of the approximated JL compared to the original JL was calculated for each segment and is subsequently referred to as JL error.…”
Section: Methodsmentioning
confidence: 99%
“…The intra-articular tibial and femoral ACL insertion points were defined based on weighted means of anatomic insertion sites as described by Parkar et al [ 24 ] who reported the tibial insertions according to Stäubli et al [ 25 ] and the femoral insertions according to Bernard et al [ 26 ], as described in a previous study [ 27 ].…”
Section: Methodsmentioning
confidence: 99%